Integrity of pipelines transporting hydrocarbons corrosion, mechanisms, control, and management - Bolzon, Gabriella (Dordrecht, Netherlands Springer, 2011)
This book describes technical and practical aspects of pipeline damage. It summarizes the phenomena, mechanisms and management of pipeline corrosion in-service. The topics discussed include pipelines fracture mechanics, damage mechanisms and evolution, and pipeline integrity assessment. The concept of acceptable risk is also elucidated and the future application of new knowledge management tools is considered.
The Use of Knowledge Management to Improve Pipeline Safety -- Development and Applications of a Specialty Nickel-Based Alloy and the Need for Corrosion Education -- Pipeline Regulation in Canada -- Fracture Mechanics Approach to Stress Corrosion Cracking of Pipeline Steels: When Hydrogen is the Circumstance -- Degradation of Properties of Long Term Exploited Main Oil and Gas Pipelines Steels and Role of Environment in this Process -- Assessment Methodologies for Girth Weld Defects in Pipelines -- Weldability of  a  Supermartensitic  Stainless Steel 12Cr4Ni1Mo Pipeline and the Effect of Welding Current on Precipitated Ferrite ? in the HAZ -- «Canadian experience in SCC of pipelines and its remedies  -Recent Progress in SCC of Pipelines in Near-Neutral pH Environment -- Hydrogen Embrittlement of Steels ? Testing and Modelling as a Joint Effort -- The Role for Material and Corrosion Engineering in Managing the Service-Life Integrity of Flow and Export Lines -- Protection for Natural Gas Installations Against the Corrosive Effect of Mercury by a Chemical Nickel Coating -- Corrosion Study of API 5L X60 Gas Pipelines Steels in NS4 Simulated Soil -- Leak Detection:  General Remarks and Examples -- Corrosion Defect Assessment on Pipes Using Limit Analysis and Notch Fracture Mechanics -- A Damage Evolution Approach in Fracture Mechanics of Pipelines -- Two Parameter Engineering Fracture Mechanics : Calculation of the Relevant Parameters and Investigation of Their Influence on the Surface Notch -- Crude-Oil Flow Modelling in Pipeline Conditions -- Corrosion Risk Assessment of Pipelines Based on Cathodic Protection Survey -- Above Ground Coating Integrity Assessment: Experience with SUMED Pipel
Electronic reproduction.
Keywords: Pipelines -- Corrosion -- Congresses; Pipelines -- Protection -- Congresses